Mitigation of erroneous oscillations in electromagnetic transient simulations using analogue filter theory - Araújo, Anderson R. J. [UNESP]; Kurokawa, Sérgio [UNESP]; Shinoda, Ailton A. [UNESP]; Costa, Eduardo C. M. (Institution of Engineering and Technology (IET), 2017)
An efficient and simplified procedure is proposed for the reduction of high-frequency oscillations and erroneous magnitude peaks in electromagnetic transient simulations in power transmission systems modelled by the lumped electric parameters approach. This procedure consists of the inclusion of analogue filters in the equivalent representation of multiconductor transmission lines without modifying its electromagnetic propagation characteristics. The analogue filter modelling is conducted as a function of the line length and line parameters. The proposed simulation methodology is applied directly in the line modelling, which means that the filtering/correction process represents a real-time process during simulations, without post-processing filtering techniques using digital filters or variations in the solution methods. The results obtained directly in the time domain by the proposed modelling/simulation methodology are compared with simulations obtained from well-established line models using the numerical Laplace transform and the Bergeron method.